2010
DOI: 10.1007/s10600-010-9568-7
|View full text |Cite
|
Sign up to set email alerts
|

New flavonoids from Punica granatum flowers

Abstract: Punica granatum Linn. (Punicaceae) is a large deciduous shrub or small tree, up to 10 m in height, that grows well in the warm valleys and hills of the Himalayas and is cultivated throughout India [1]. In traditional Ayurvedic medicine, all parts of P. granatum are used for the treatment of various disorders [2]. The flowers of P. granatum are used in folk medicine for the treatment of bronchitis, diarrhea, dysentery, ulcers, hepatic damage, sore eyes, and diabetes [3,4]. Phytochemical investigation of P. gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…According to the results (Table 1) and additional 2D NMR experimens performed by us, which agreed with results from an analogous analysis of a similar structure [30], the chemical shifts and SSCC for the protons (characteristic [24] of H-2E, H-3 ax , and H-3 eq ) of the ABX system of flavanone 8 ring C belonged to the 2S-isomer.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…According to the results (Table 1) and additional 2D NMR experimens performed by us, which agreed with results from an analogous analysis of a similar structure [30], the chemical shifts and SSCC for the protons (characteristic [24] of H-2E, H-3 ax , and H-3 eq ) of the ABX system of flavanone 8 ring C belonged to the 2S-isomer.…”
supporting
confidence: 88%
“…An ABX system was observed in the PMR spectrum as a doublet of doublets with chemical shifts G 5.43, 3.26, and 2.68 ppm with SSCC characteristic of the H-2E, H-3 ax , and H-3 eq protons of flavanone ring C [24].…”
mentioning
confidence: 99%
“…Inhibition of inflammation by pomegranate components involves inhibition of both COX and LOX enzymes (Schubert et al, 1999) and a decline in prostaglandin release from cells (Polagruto et al, 2003). The phytochemical analysis of flower extract also revealed that it contains flavonoids characterized as 5,6,7,8,2′,3′,5′-heptahydroxy-4′-methoxyflavanone (punicaflavanol) and 5,6,7,8,2′,5′hexahydroxy-4′-methoxyflavanone -7-β-D-xylopyranoside (granatumfla vanyl xyloside) (Bagri et al, 2010). Flavonoids are well known for their ability to inhibit pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Two flavones, luteolin and tricetin, were found in a methanolic extract of pomegranate flowers [ 23 ]. Structures of two flavanones, punicaflavanol (a misnomer; it is a flavanone) and granatumflavanyl xyloside, were elucidated by NMR [ 25 ], while hovetrichoside C (a glycoside of an auronol) and phlorizin (a glycoside of the dihydrochalone phloretin) were identified by IR in pomegranate flowers [ 24 ].…”
Section: Occurrence and Structure Of Diverse Phytochemicals In Pommentioning
confidence: 99%